DETERMINATION OF ANTIRADICAL ACTIVITY OF PLANT EXTRACTS (Scientific journal of the Fergana State University, 2024)
This article examines the antiradical activity (ARA) of pine pollen and plant extracts from eastern biota in relation to the free radical 2,2-diphenyl-1-picrylhydrazyl (DPPH). Quantitative characteristics of the reaction of DPPH reduction by the studied substances were determined. To evaluate ARF in this process, we used spectrophotometric measurements of the reduction kinetics of stable radical molecules 2,2-diphenyl-1-picrylhydrazyl (DPPG) by antioxidants. It was found that the studied compounds have a high ability to remove free radicals.